One-Year Efficacy and Safety of Combined Photorefractive Keratectomy and Accelerated Corneal Collagen Cross-Linking after Intacs SK Intracorneal Ring Segment Implantation in Moderate Keratoconus. (8th July 2019) - Koh, Il Hwan; Seo, Kyoung Yul; Park, Seong Bae; Yang, Hun; Kim, InSik; Kim, Jin Sun; Hwang, David G.; Nam, Sang Min
Abstract : Purpose . To report one-year outcomes of a modified version of two-stage multimodal surgical protocol for moderate keratoconus which has been suggesting promising preliminary results. Materials and Methods . 30 eyes of 25 patients with moderate keratoconus who exhibited visual complaints and/or disease progression were included for this retrospective case study. Approximately 3 months after implantation of intracorneal ring segment (Intacs SK™), a combination of corneal wavefront-guided transepithelial photorefractive keratectomy (CWG-transPRK, Schwind Amaris® 1050, and Schwind Sirius) and accelerated collagen cross-linking (accCXL, Avedro KXL™) was performed. Patients were examined for uncorrected and corrected distance visual acuity (UDVA; CDVA), keratometric power (K), corneal thickness, and corneal higher-order aberrations (HOAs) preoperatively and at postoperative 1, 3, 6, and 12 months. Results . The median UDVA and mean CDVA were enhanced from 6/38 to 6/12 and from 6/19 to 6/7.5, respectively, through 12 months after CWG-transPRK/accCXL. The 12-month CDVA of all patients was better than 6/12 Snellen, and no subject lost one or more lines of CDVA. The magnitudes of both myopia and corneal steepness were decreased in turn by Intacs SK implantation and also by CWG-transPRK/accCXL, but the reduction in HOA was largely the result of CWG-transPRK/accCXL. The magnitude of corneal thinning stabilized within 3 months after CWG-transPRK/accCXL. Conclusion . This approach may allow patients with moderate keratoconus to obtain satisfactory vision without the need for contact lens wear. This surgery appeared to be effective and safe through 1 year of follow-up.